2014
DOI: 10.1128/jb.01551-14
|View full text |Cite
|
Sign up to set email alerts
|

EscO, a Functional and Structural Analog of the Flagellar FliJ Protein, Is a Positive Regulator of EscN ATPase Activity of the Enteropathogenic Escherichia coli Injectisome

Abstract: Type III secretion systems (T3SSs) are multiprotein molecular devices used by many Gram-negative bacterial pathogens to translocate effector proteins into eukaryotic cells. A T3SS is also used for protein export in flagellar assembly, which promotes bacterial motility. The two systems are evolutionarily related, possessing highly conserved components in their export apparatuses. Enteropathogenic Escherichia coli (EPEC) employs a T3SS, encoded by genes in the locus of enterocyte effacement (LEE) pathogenicity i… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1

Citation Types

3
46
0

Year Published

2015
2015
2021
2021

Publication Types

Select...
6
1

Relationship

3
4

Authors

Journals

citations
Cited by 26 publications
(49 citation statements)
references
References 89 publications
3
46
0
Order By: Relevance
“…It has been reported that functionally related T3SS-associated proteins, despite not having significant sequence similarity, are encoded by genes with similar genetic contexts (32,57,66,67). Our BLAST search identified multiple uncharacterized EscK homologs encoded by genes sharing the same context as that for genes coding for members of the SctK family (YscK, MxiK, and OrgA) (68).…”
Section: Discussionmentioning
confidence: 92%
See 2 more Smart Citations
“…It has been reported that functionally related T3SS-associated proteins, despite not having significant sequence similarity, are encoded by genes with similar genetic contexts (32,57,66,67). Our BLAST search identified multiple uncharacterized EscK homologs encoded by genes sharing the same context as that for genes coding for members of the SctK family (YscK, MxiK, and OrgA) (68).…”
Section: Discussionmentioning
confidence: 92%
“…The escK gene is located downstream of the cesAB gene, encoding a chaperone for the EspA and EspB translocators (50), and upstream of escL, encoding a member of the SctL protein family that acts as a negative regulator of EscN ATPase activity (32). Likewise, the genes located downstream of the identified escK homologs (Fig.…”
Section: Resultsmentioning
confidence: 99%
See 1 more Smart Citation
“…A key component of the export apparatus is a cytoplasmic nonameric ring structure called the export gate, which localizes to the base of the basal body and is proposed to sequester effectors prior to secretion (3). The ATPase (called EscN in EPEC) forms complexes with its positive and negative regulators, EscO and EscL, respectively (4). EscN is one of the best-characterized T3SS ATPases and is suggested to form a hexameric ring structure, analogous to that of the F o F 1 -ATPase, with ATP bound between adjacent monomers (5).…”
mentioning
confidence: 99%
“…The peripheral stalk, EscL, inhibits the EscN ATPase activity and may form a trimeric heterocomplex with EscN and EscO, resembling the homologous flagellar FliH-FliI-FliJ complex (19). Based on the structural and functional similarities of the T3SS and flagellar ATPase complexes, EscL is predicted to bind the N-terminal region of EscN, while EscO binds the C-terminal region of EscN (4,20). EscL and EscO are linked to the export gate while holding the EscN ATPase far from the export gate in an export-off state (6) (Fig.…”
mentioning
confidence: 99%